1997
DOI: 10.1046/j.1365-2346.1997.00111.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the negative inotropic effect of midazolam and diazepam in cultured foetal mouse cardiac myocytes

Abstract: We have investigated the effects of midazolam and diazepam on intracellular calcium (Ca2+) handling in foetal mouse ventricular myocytes using the Ca(2+)-sensitive fluorescent indicator, indo-1. We also investigated separately whether flumazenil or the L-type Ca2+ channel agonist, Bay K8644, antagonized these myocardial depressive effects. Midazolam and diazepam decreased the Ca2+ transient and beating rate in a concentration-dependent manner, and these decreases were prevented by Bay K8644. Flumazenil did not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 27 publications
(1 reference statement)
0
8
0
Order By: Relevance
“…10,11 In fact, our patient was noted to develop second-degree Mobitz Type 1 AV block on a rhythm strip performed approximately 30 minutes after flumazenil administration. Flumazenil did not correct the EKG changes in Case 1 despite reversal of his respiratory and central nervous system depression.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…10,11 In fact, our patient was noted to develop second-degree Mobitz Type 1 AV block on a rhythm strip performed approximately 30 minutes after flumazenil administration. Flumazenil did not correct the EKG changes in Case 1 despite reversal of his respiratory and central nervous system depression.…”
Section: Discussionmentioning
confidence: 79%
“…[8][9][10][11] Flumazenil inconsistently reverses this decrease. [8][9][10][11] Flumazenil inconsistently reverses this decrease.…”
Section: Discussionmentioning
confidence: 94%
“…Some studies have reported blood pressure reductions after midazolam induction for ICU sedation or pre-hospital rapid sequence induction [ 9 , 10 ]. Given its anxiolytic and sedative properties, midazolam has negative inotropic activity in atrial tissues mediated by the inhibition of L-type calcium channels [ 11 ]. However, although dexmedetomidine and midazolam reduce blood pressure and heart rate, a previous comparative study demonstrated lower heart rate and blood pressure during third molar surgery for dexmedetomidine compared to midazolam during monitored anesthesia care [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The effects of diazepam on the AP were very close to those of nicardipine. Indeed, diazepam was found to have calcium‐blocking properties on cardiac cells (Nonaka et al ., 1997). Propranolol and phenytoin were also found to cause a concentration‐dependent triangulation that seems to be related to an effect on the depolarising sodium current, as suggested by the decrease in V max caused by these compounds.…”
Section: Discussionmentioning
confidence: 99%